STRATEGI PENGEMBANGAN USAHA TAHU PADA INDUSTRI TAHUâVIVIâDI KOTA PALU - Nurlina, Nurlina; Lamusa, Arifuddin (AGROTEKBIS, 2018)
Tofu industry "Vivi" is one of the industries that produce soy-based products locatedinBuah Pala street No. 9 Boyaogevillage Tatangasub district of Palu city, Central Sulawesi. This study aimed to determine the revenue earned by thetofu industry "Vivi" and to determine the development strategy of the industry. The results of the analysis showed that the income earned by the tofu industry "Vivi" during January to February was IDR32,318,058. Based on the SWOT analysis,it can be concluded that the position of business development strategies in the tofu industry "Vivi" was in quadrant one suggesting that the focused strategy for business development oftofu industry "Vivi" is S-O strategy indicating that the industry should use all its strengths to seize and exploit opportunities facing. Keywords: Business development strategy, Soy, and Tofu industry "Vivi".